Approaches to Language Education and Schooling in Post-Conflict Phase in Georgian Contexts - Shalva Tabatadze (Universitas Negeri Makassar, 2022)
Language education and schooling are important topics in post-conflict contexts. This study explores the existing situation of mother tongue education in the de facto Abkhazia. The study had the following research questions: (1) What was the ethnic composition of Abkhazia during the Soviet Union and how Russian occupation changed it? (2) How well is the ethnic composition of the occupied territory of Abkhazia reflected in language schooling? (3) What type of language education policy is used in Abkhazia? The research revealed that the opportunity of mother tongue education is restricted for minority as well as majority ethnic groups in Abkhazia. Based on this finding, a new language education policy approach emerged. The language education policy in de facto Abkhazia is classified as “Occupational Approach